Catalysis at the heart of success! - Bornscheuer, Uwe Theo; Hashmi, A. Stephen K. (ChemCatChem, 2017)
Rapid Development, New Challenges, and Fascinating Times: New co-Chairmen have been elected for the next generation. The co-Chairmen of ChemCatChem address their roles and their outlook on catalysis.
Gesehen am 26.04.2018